Plugging in and into code bubbles: the code bubbles architecture. (21st May 2013) - Reiss, Steven P.; Bott, Jared N.; La Viola, Joseph J.; Garbervetsky, Diego; Kim, Sunghun
ABSTRACT Code Bubbles is an attempt to redefine the user interface for an integrated programming environment. As it represents a whole new user interface, implementing it as a plug‐in is inherently difficult. We get around this difficulty by combining two different plug‐in architectures, a standard one based on registrations and callbacks and a message‐based one that puts the plug‐in at arm's length and defines a narrower two‐way interface. This paper describes both how we have implemented Code Bubbles as a plug‐in to Eclipse and how Code Bubbles itself is implemented as a set of plug‐ins representing the different aspects of the environment, using both traditional and message‐based plug‐in architectures as appropriate. It also shows how the resultant architecture is flexible enough to support collaboration, different back ends, and a cloud‐based environment. Copyright © 2013 John Wiley & Sons, Ltd.